Implementasi Total Quality Management dan Teamwork Melalui Budaya Organisasi Dalam Meningkatkan Kinerja Manajerial di Lingkungan Rsud Sunan Kalijaga Kabupaten Demak - Aini, Akhmad Nur; Utomo, Joko; Purwoatmodjo, Djumadi (Universitas Muria Kudus, 2021)
This research has the purpose of examining the implementation of Total Quality Management and Teamwork through organization culture in improving managerial performance in the neighborhood of Sunan Kalijaga District of Demak. The research population is 276 employees. Sample of 220 respondents. Data types and resources use primary data and secondary data. Test instruments using validity tests, reliability tests. Data analysis using SEM AMOS version 23. Based on the results of the study concluded that Total Quality Management, Team Work directly influence positive and significant of organizational culture and managerial performance. Indirectly the organizational culture variables are able to provide added value or become a mediation variable between Total Quality Management, Team Work to managerial performance.Penelitian ini mempunyai tujuan meneliti Implementasi Total Quality Management dan Teamwork melalui Budaya Organisasi dalam Meningkatkan Kinerja Manajerial di Lingkungan RSUD Sunan Kalijaga Kabupaten Demak. Populasi penelitian sebanyak 276 pegawai. Sampel sebanyak 220 responden. Jenis dan sumber data menggunakan data primer dan data sekunder. Uji instrument menggunakan uji validitas, uji reliabilitas. Analisis data menggunakan SEM AMOS versi 23. Berdasarkan hasil penelitian menyimpulkan bahwa Total Quality Management, Team Work berpengaruh secara langsung positif dan signifikan terhadap budaya organisasi dan kinerja manajerial. Secara tidak langsung variabel budaya organisasi mampu memberikan nilai tambah atau menjadi variabel mediasi antara Total Quality Management, Team Work terhadap Kinerja Manajerial.